PENERAPAN SUPERVISI AKADEMIK UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN KURIKULUM 2013 - Idaham Idaham (FKIP ULM, 2020)
This study aims to improve teachers' ability to compile the lesson plan based on the 2013 curriculum through academic supervision at SDN Kepayang Tapin Regency. This research is a school action research conducted in two cycles. The subjects of this study were the three teachers (teachers grade 1, 2, and 3 at SDN Kepayang. The instrument used was the planning of the lesson plan observation sheet and the implementation of the lesson plan observation sheet. Quantitative descriptive techniques analyzed data. The results showed the ability of classroom teachers in developing lesson plans based on the curriculum in 2013 of five indicators are considered: (1) the percentage of individual completeness of 63.4 and classical completeness of 33.33 in cycle 1; (2) the percentage of individual completeness 76 and classical completeness of 100 in cycle 2. Based on the research results, it can be concluded that academic supervision can improve classroom teachers' ability to prepare lesson plans based on the 2013 curriculum.Keywords: Academic Supervision; 2013 Curriculum; Lesson plan; Teacher AbilityAbstrak. Penelitian ini bertujuan meningkatkan kemampuan guru dalam menyusun Rencana Pelaksanaan Pembelajaran (RPP) berdasarkan kurikulum 2013 melalui supervisi akademik di Sekolah Dasar Negeri (SDN) Kepayang Kabupaten Tapin. Penelitian adalah penelitian tindakan sekolah yang dilaksanakan sebanyak dua siklus. Subjek penelitian ini adalah tiga orang guru (guru kelas 1, 2, dan 3) di SDN Kepayang. Instrumen yang digunakan adalah lembar observasi perencanaan RPP dan lembar observasi keterlaksanaan RPP. Data dianalisis dengan menggunakan teknik deskriptif kuantitatif. Hasil penelitian menunjukkan kemampuan guru kelas dalam menyusun RPP berdasarkan kurikulum 2013 dari lima indikator yang dinilai yaitu (1) persentase ketuntasan individual 63,4 dan ketuntasan klasikal 33,33 pada siklus 1; (2) persentase ketuntasan individual 76 dan tuntas secara klasikal 100 pada siklus 2. Berdasarkan hasil penelitian dapat disimpulkan supervisi akademik dapat meningkatkan kompetensi guru kelas dalam menyusun RPP berdasarkan kurikulum 2013. Kata Kunci: Supervisi Akademik; Kurikulum 2013; Rencana Pelaksanaan Pembelajaran;Kemampuan Guru